2009
DOI: 10.1002/app.30595
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation analysis of polyamide 6 processed at different cycles using sequential pyrolysis

Abstract: The principal product from the degradation of polyamide 6 (PA6) is caprolactam, which is a consequence of the intramolecular exchange (cyclization) of PA6. The information obtained from certain thermal analysis techniques, such as differential scanning calorimetry (DSC), is not sufficiently detailed to study the degradation suffered by PA6 in function of these processes, whereas the study of this degradation using other more precise techniques (sequential pyrolysis) and the application of models (Guggenheim an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…As expected, a second heating scan showed no significant effect on the glass transition of the filled PA6. [ 56 ] The addition of fibers to the neat PA6 shifts the Tg to higher temperatures in the first heating scan. The baseline shift is more significant for the filled polymer as the fibers intensify the signal, and thus, no Tg was visible for the neat PA6 in the second heating scans.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As expected, a second heating scan showed no significant effect on the glass transition of the filled PA6. [ 56 ] The addition of fibers to the neat PA6 shifts the Tg to higher temperatures in the first heating scan. The baseline shift is more significant for the filled polymer as the fibers intensify the signal, and thus, no Tg was visible for the neat PA6 in the second heating scans.…”
Section: Resultsmentioning
confidence: 99%
“…Greatly elevated heating rates shift the melting point to higher temperatures, while the second heating cycle, performed for the standard heating rates, shifted it to slightly lower temperatures as expected. [ 56 ] It is suggested that this results from the induced increase in crystallinity during controlled cooling in the first cycle. The addition of fibers to PA6 showed no significant change to the melting temperature at the standard heating rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal characterization of PA6 based SPC and the recycled composites was carried out to detect the threshold temperatures in the fabrication process applied. Thermal degradation of PA6 has been studied sufficiently [32][33][34][35] showing that it is strongly depended on the temperature and the presence of a nucleophile (i.e. water).…”
Section: Thermal Characterization By Combined Tga/dtamentioning
confidence: 99%